Altered Intra- and Inter-regional Functional Connectivity of the Anterior Cingulate Gyrus in Patients With Tremor-Dominant Parkinson’s Disease Complicated With Sleep Disorder - Chen, Xinjie; Hou, Xiaoyan; Luo, Xiaodong; Zhou, Sifan; Liu, Xian; Liu, Bo; Chen, Jun (Frontiers in Aging Neuroscience, 2019)
Abstract Objective: To investigate changes in brain function at the regional and whole-brain levels in patients with tremor-dominant Parkinson's disease (TDPD) complicated by sleep disorder (SD) by regional homogeneity (ReHo) and functional connectivity (FC) analysis of whole-brain resting-state functional magnetic resonance images. Materials and methods: ReHo and seed-based FC analyses were conducted among 32 patients with TDPD and SD (TDPD-SD), 24 with TDPD and no SD (TDPD-NSD), and 23 healthy controls (HC) to assess spontaneous brain activity and network-level brain function. Correlation analyses were used to examine the associations between brain activity and the clinical data. Results: Anterior cingulate gyrus (ACC) ReHo values differed significantly among the groups. ACC ReHo values were increased in TDPD-SD versus HC and TDPD-SD versus TDPD-NSD. ACC ReHo values were reduced in TDPD-NSD versus HC. TDPD-SD ReHo values were positively correlated with Pittsburgh Sleep Quality Index (PSQI) scores (r=0.41, p=0.020) but negatively correlated with Parkinson's Disease Sleep Scale (PDSS) scores (r=-0.38, p=0.030). FC analysis using ACC as a mask showed that FC of the left olfactory cortex (L-OC), right straight gyrus (R-SG), right superior parietal gyrus (R-SPG), and right precuneus differed significantly among the groups. FC values between R-SG and ACC were significantly lower in TDPD-SD than in TDPD-NSD, while the FC of L-OC and R-OC with ACC was significantly lower in TDPD-SD than in HC. FC between ACC and L-OC, R-SPG, and the right precuneus was lower in TDPD-NSD than in HC. There was no correlation between the FC values and other clinical data in any of the groups. Conclusion: Localized abnormal activity in TDPD-SD was chiefly triggered by ACC. The change in the ReHo of ACC is closely related to the severity of TDPD-associated SD, revealing the role of this region as a regulator of the sleep mechanism in TDPD. Significant abnormal FC was found between R-SG and ACC in TDPD-SD but was not shown to correlate with clinical data.